Meso‐Functionalization of Silk Fibroin by Upconversion Fluorescence and Near Infrared In Vivo Biosensing. (3rd May 2017) - Song, Yang; Lin, Zaifu; Kong, Lingqing; Xing, Yao; Lin, Naibo; Zhang, Zhisen; Chen, Bing‐Hung; Liu, Xiang‐Yang
Abstract : In biomedical applications, it is very desirable to monitor the in vivo state of implanted devices, i.e., tracking the location, the state, and the interaction between the implanted devices and cell tissues. To achieve this goal, a generic strategy of soft materials meso‐functionalization is presented. This is to acquire silk fibroin (SF) materials with added functions, i.e., in vivo bioimaging/sensing. The functionalization is by 3D materials assembly of functional components, lanthanide(Ln)‐doped upconversion nanoparticles (UCNPs) on the mesoscopic scale to acquire upconversion fluorescent emission. To implement the meso‐functionalization, the surfaces of UCNPs are modified by the hydroxyl groups (OH) from SiO2 or polyethylene glycol coating layers, which can interact with the carbonyl groups (CO) in SF scaffolds. The functionalized silk scaffolds are further implanted subcutaneously into mice, which allows the silk scaffolds to have fluorescent in vivo bioimaging and other biomedical functions. This material functionalization strategy may lead to the rational design of biomaterials in a more generic way. Abstract : Bioimaging for silk fibroin scaffolds is achieved by the incorporation of surface‐modified upconversion nanoparticles into the mesoscopic structure of silk fibroin materials via mesoscopic materials assembly. This allows real‐time, non‐invasive imaging in vivo.